VD_FINDINFO Arrêt / 2022 / 644 vom 14. Juli 2022 - VD Tribunal cantonal (2022)
AVS, CAISSE DE COMPENSATION{AVS/AI}, PRESTATION D'ASSURANCE{AVS/AI/PC}, ACTIVITÉ LUCRATIVE DÉPENDANTE, ACTIVITÉ LUCRATIVE INDÉPENDANTE, INFORMATICIEN, EMPLOYEUR, SUISSE{ÉTAT}, MANDANT | 1 LAVS, 3 LAVS, 5 LAVS, 9 LAVS, 10 LPGA, 12 LPGA